2011
DOI: 10.1021/nl2032487
|View full text |Cite
|
Sign up to set email alerts
|

Selective Trapping and Manipulation of Microscale Objects Using Mobile Microvortices

Abstract: Controlled manipulation of individual micro- and nanoscale objects requires the use of trapping forces that can be focused and translated with high spatial and time resolution. We report a new strategy that uses the flow of mobile microvortices to trap and manipulate single objects in fluid with essentially no restrictions on their material properties. Fluidic trapping forces are generated toward the center of microvortices formed by magnetic microactuators, that is, rotating nanowire or self-assembled microbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
129
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(134 citation statements)
references
References 33 publications
(45 reference statements)
3
129
1
Order By: Relevance
“…Vortex centers with minimal flow velocity have been shown to be stable trapping positions for objects by Petit et al, 14 with abundant experimental cases, but to the best of our knowledge no clear theoretical analysis. In our case, the dynamics may be understood by a combination of viscous force along the flow direction (F V = 3πηvD, where η denotes fluid viscosity, v denotes the flow velocity and D is the 'effective' diameter of particle), and inertial force directing along the velocity gradient (F I = Re·F V , where Re denotes Reynolds number).…”
Section: Theoretical Analysismentioning
confidence: 92%
See 2 more Smart Citations
“…Vortex centers with minimal flow velocity have been shown to be stable trapping positions for objects by Petit et al, 14 with abundant experimental cases, but to the best of our knowledge no clear theoretical analysis. In our case, the dynamics may be understood by a combination of viscous force along the flow direction (F V = 3πηvD, where η denotes fluid viscosity, v denotes the flow velocity and D is the 'effective' diameter of particle), and inertial force directing along the velocity gradient (F I = Re·F V , where Re denotes Reynolds number).…”
Section: Theoretical Analysismentioning
confidence: 92%
“…16,17 Because of small and limited scale, vortices of this type were generally applied to low throughput manipulation. Abundant experimental cases 14,15 have shown that individual trapping at the vortex center is stable, but to the best of our knowledge no clear theoretical analysis has been given. The other type is through buoyancy convection, generated by thermal gradient in the liquid from opto-electrical, 18 − 22 or plasmonic 23 heating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are utilized for on-chip microcentrifuges [8][9][10], to focus or separate particles [11][12][13], to manipulate cells [7,14], to trap particles [15,16], to enrich rare cells, e.g., circulating tumor cells [17,18], to fabricate micromixers [19][20][21], to synthesize size-controlled nanoparticles [22], or to extract plasma from blood [23,24]. All these works rely on the efficient generation of microvortices.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several reports have described the potential use of NiNW as magnetic tweezers for cell manipulation under low-strength magnetic fields. Examples include the possibility to handle cellular and subcellular objects in aqueous environments by rotating magnetic NiNW [23], the controlled manipulation of micro-and nano-scale objects by using mobile microvortices generated by rotating nanowires [24], and the use of such rotating Ni NW for propulsion and cargo transport [25].…”
Section: Introductionmentioning
confidence: 99%